(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The relationship between individuals and society has always been one of the most important themes in literature. Literary works reflect social reality and help readers understand the complex interactions between individuals and the communities in which they live. In many literary traditions, the depiction of social relations serves as a means of analyzing moral values, cultural traditions, and the psychological conflicts that arise within society. Uzbek literature of the twentieth century developed significantly in addressing these themes and portraying the transformation of social life.Shukur Kholmirzayev is considered one of the most prominent representatives of modern Uzbek prose. His literary works portray the lives of ordinary people and their interactions with the social environment. The writer carefully depicts the influence of social norms, traditions, and cultural values on the formation of human character and identity. Through his stories and novellas, Kholmirzayev reveals the psychological struggles of individuals who attempt to balance personal aspirations with societal expectations. This article examines the artistic interpretation of human–society relations in the works of Shukur Kholmirzayev. The research focuses on the depiction of human psychology, the role of social environment, and the representation of moral values in the writer’s narratives. Particular attention is given to the way in which the author portrays social conflicts, ethical dilemmas, and the transformation of human identity in different social contexts.The study demonstrates that Kholmirzayev’s works contribute significantly to the development of Uzbek realistic prose. His literary heritage provides valuable insights into the relationship between individuals and society and reflects the social and cultural dynamics of Uzbek life.